Asthma management self-efficacy in parents of primary school-age children. (June 2014) - Brown, Nicola; Gallagher, Robyn; Fowler, Cathrine; Wales, Sandra
The aim of this study was to investigate asthma management self-efficacy in parents of primary school-age children with asthma and to explore possible associations between parent asthma management self-efficacy, parent and child characteristics, asthma task difficulty and asthma management responsibility. A cross-sectional descriptive survey of 113 parents was conducted to assess the level of parent asthma management self-efficacy, asthma task difficulty and confidence, asthma responsibility and socio-demographic characteristics. The findings indicate that parents had higher self-efficacy for attack prevention than attack management. Parents had higher self-efficacy for asthma management tasks that are simple, skills based and performed frequently such as medication administration and less confidence and greater difficulty with tasks associated with judgement and decision-making. Multivariate linear regression analysis identified English language, child asthma responsibility and parent education as predictors of higher asthma management self-efficacy, while an older child was associated with lower parent asthma management self-efficacy. The implications of these results for planning and targeting health education and self-management interventions for parents and children are discussed.